James of Viterbo on Seminal Reasons as inchoationes formarum - Gossiaux, Mark (Vivarium, 2021)
Abstract This article examines James of Viterbo’s theory of seminal reasons as inchoate forms ( inchoationes formarum ). James intends this theory to explain how the eduction ( eductio ) of substantial forms from the potency of matter does not entail that such forms are created ex nihilo . Substantial forms that come to be in generation preexist in matter as forms in potency. The form in potency is an inchoation of, or aptitude or propensity for, the form that comes to be in act. Generation is thus understood by James to be a modal change, for the form in potency and the form in act are one and the same thing ( res ); they differ only with regard to their mode of being. James’s theory of inchoate forms is a development of Bonaventure’s theory of seminal reasons, but reformulated with the help of Simplicius and Averroes.